2014
DOI: 10.1111/ijcp.12433
|View full text |Cite
|
Sign up to set email alerts
|

Safety and tolerability of the β 3 ‐adrenoceptor agonist mirabegron, for the treatment of overactive bladder: results of a prospective pooled analysis of three 12‐week randomised Phase III trials and of a 1‐year randomised Phase III trial

Abstract: SUMMA RYAims: To evaluate the safety and tolerability of the b 3 -adrenoceptor agonist, mirabegron, in patients with overactive bladder (OAB). Methods: Tolerability and safety data from three 12-week, randomised, placebo-controlled, double-blind, Phase III trials (Studies 046, 047 and 074) were pooled by treatment group. The three studies were of a similar design, although the assessed doses of mirabegron [25, 50 or 100 mg once daily (qd)] varied, and tolterodine extended release (ER) 4 mg was included as an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
38
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(45 citation statements)
references
References 49 publications
3
38
0
4
Order By: Relevance
“…Treatment with mirabegron was not associated with an increased risk of hepatic or other laboratory disturbances, or an increased rate of cardiovascular adverse events relative to placebo or tolterodine ER [19]. Tachycardia TEAEs were experienced by a small (1.2 %) proportion of patients receiving mirabegron 50 mg/day in the 12-month study [19].…”
Section: Is Mirabegron Effective In Older Patients?mentioning
confidence: 91%
See 3 more Smart Citations
“…Treatment with mirabegron was not associated with an increased risk of hepatic or other laboratory disturbances, or an increased rate of cardiovascular adverse events relative to placebo or tolterodine ER [19]. Tachycardia TEAEs were experienced by a small (1.2 %) proportion of patients receiving mirabegron 50 mg/day in the 12-month study [19].…”
Section: Is Mirabegron Effective In Older Patients?mentioning
confidence: 91%
“…Mirabegron 50 mg once daily was generally well tolerated, with most treatment-emergent adverse events (TEAEs) being of mild or moderate severity [19].…”
Section: Is Mirabegron Effective In Older Patients?mentioning
confidence: 99%
See 2 more Smart Citations
“…31 The pooled analysis also demonstrated that the tolerability profile of mirabegron was similar to that of placebo and tolterodine ER 4 mg, with the exception of dry mouth, where the incidence was five times higher with tolterodine ER 4 mg than with mirabegron. 32 In a review of clinical trials of up to 12 months, the most common adverse events (AEs) observed with mirabegron were hypertension, nasopharyngitis, and urinary tract infection. 33 Real-world experience (based on data from >19 000 patients treated for OAB in Canada) indicates that mirabegron provides greater persistence and adherence than antimuscarinic agents.…”
Section: Introductionmentioning
confidence: 99%